2007
DOI: 10.1016/j.bioorg.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput screening approach to anthrax lethal factor inhibition

Abstract: A high-throughput screening approach was used to identify new inhibitors of the metallo-protease lethal factor from Bacillus anthracis. A library of ~14,000 compounds was screened using a fluorescence-based in vitro assay and hits were further characterized enzymatically via measurements of IC 50 and K i values against a small panel of metallo-proteases. This study led to the identification of new scaffolds that inhibit LF and the Botulinum Neurotoxin Type A in the low micromolar range, while sparing the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Other groups have screened chemical libraries with a variety of read-outs for the in vitro proteolytic activity of LF (Panchal et al, 2004;Lee et al, 2004;Min et al, 2004;Forino et al, 2005;Fridman et al, 2005;Kocer et al, 2005;Johnson et al, 2007Johnson et al, , 2009. A phenylfuran-2-ylmethylenerhodanineacetic acid derivative (B1-11B3) showed a good inhibition constant in vitro (K i = 32 nM) and gave a synergistic protection with ciprofloxacin in an anthrax mouse model (Forino et al, 2005).…”
Section: Inhibitorsmentioning
confidence: 99%
“…Other groups have screened chemical libraries with a variety of read-outs for the in vitro proteolytic activity of LF (Panchal et al, 2004;Lee et al, 2004;Min et al, 2004;Forino et al, 2005;Fridman et al, 2005;Kocer et al, 2005;Johnson et al, 2007Johnson et al, , 2009. A phenylfuran-2-ylmethylenerhodanineacetic acid derivative (B1-11B3) showed a good inhibition constant in vitro (K i = 32 nM) and gave a synergistic protection with ciprofloxacin in an anthrax mouse model (Forino et al, 2005).…”
Section: Inhibitorsmentioning
confidence: 99%
“…The LF inhibitors identified thus far contain key Zn 2+ -chelating moieties7 such as a hydroxymate813, polyphenols/catechol14,15, penicillin based16, rhodanine17,18,14,6,19, aminoglycoside2022, quinoline urea23, and hydrazone24,25. In this study, we present the identification of a novel scaffold shown to inhibit LF in vitro and in cell .…”
Section: Resultsmentioning
confidence: 95%
“…In this study, we present the identification of a novel scaffold shown to inhibit LF in vitro and in cell . This scaffold was identified via screening a diverse chemical library of 16,000 drug-like molecules (HitFinder ™ , Maybridge, Morris Plains, NJ) utilizing high-throughput fluorescence microplate assays as previously described17,14,18. Kinetic studies of the most potent LF inhibitors with >50% inhibition at 20 μM, were performed and IC 50 and K i values were obtained by dose response measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The bis-quinoline 1 is the screening hit 33 around which we began our synthetic efforts of hit and lead optimization. Benzopyranone 2 34 was shown to be an inhibitor of Botulinum neurotoxin A in addition to LF. A class of acylhydrazones represented by compound 3 also blocked the cleavage of MEK1 in 293T cells.…”
Section: Introductionmentioning
confidence: 99%